Curva de crescimento do capim annoni - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The invasor species called South African lovegrass (Eragrostis plana Ness) has been representing a significant threat to the animal production in the southern states of Brazil. Therefore, it becomes of relevant importance further information about the growth and development of this plant so harmful to the development of native species of the biome pampa. However, this study aimed to evaluate the growth of South African lovegrass during the summer growing season in the city of Itaqui-RS. Was sown on August 29, 2015 in previously filled trays with substrate after the emergence of plants these were transplanted after a period of seven days for vessels with volume capacity of eight liters, seven days after transplantation was thinning plants made, leaving remaining one plant each. They were determined eight treatments, each treatment represented by a weekly evaluation, with four replicates per treatment, totaling thirty-two experimental units, the experimental design was completely randomized (DCR). The collected plants were conducted measurements of shoot height and length of root system, they were later taken to the oven with forced air circulation at a temperature of 65 °C for a period of 96 hours, in order to get the content matter dry plants. The growth South African lovegrass during the study period is different depending on the measured variable.
Keywords: Desenvolvimento; Temperaturas; Épocas do ano; Development; Temperature; Year season; Eragrostis plana Ness; CNPQ::CIENCIAS AGRARIAS